Analisis Penerapan Literasi Keuangan pada Pendidikan Anak Usia Dini (Studi : Paud Insan Cendikia Harapan Rejo Lampung Tengah) - Husada, Hindiana Sava; Zesika, Ardetia Lara; Riani, Novi (STIES ALIFA, 2024)
The implementation of financial literacy from an early age is a strategic effort to instill understanding and positive habits related to money management in children. This study aims to analyze how financial literacy is implemented in early childhood education at PAUD Insan Cendikia, Harapan Rejo, Central Lampung. A qualitative approach was employed, with data collected through interviews, observations, and documentation. The research subjects consisted of teachers and parents of the students. The results indicate that financial literacy is applied through a play-based learning approach using the Beyond Center and Circle Time (BCCT) model. Financial literacy activities include the introduction of money, managing pocket money, saving habits, socio-drama on buying and selling, visits to BRILink agents, and the instilling of values such as sharing and entrepreneurship. This implementation also involves the active participation of parents as the primary companions. The study concludes that PAUD Insan Cendikia has implemented a structured and comprehensive financial literacy program, although challenges remain in maintaining consistent parental involvement and strengthening children's understanding of needs versus wants.